Between Profit and Quality; A Challenge of Indonesian Cinema - Puji Lestari; Lambok Hermanto Sihombing (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
Horror is one of the most popular film genres, particularly among Indonesians. One of the reasons the Indonesian people love watching a horror movie is because of the sensation of a jump scare. Thus, the number of horror film watchers in Indonesia continues to grow. This condition may aid Indonesian film production, as practically everyone enjoys horror. However, it is also problematic because Indonesian film has struggled to enhance its quality. Thus, the author's objective in this study is to analyse the dilemma confronting Indonesian cinema: the trade-off between profit and quality. To assist the author in doing this analysis, Film Production Management from Bastian Cleve is applied. The findings of this study reveal that Indonesian film production faces particular challenges that must be overcome. Indonesian cinema should prioritize quality above immediate profit as improving the quality of a film can result in a higher profit. Thus, the courage to develop and compete is critical to overcome those challenges.